Reporting Sexual Victimization During Incarceration: A National-Level Assessment of Formal Reporting in Jails - Freemon, Kayla (Crime & delinquency, 2025)
The National Inmate Survey estimates over 22,000 individuals in United States jails were sexually victimized between 2011 and 2012. However, most incidents were never formally reported to correctional authorities. Empirical analysis of this reporting gap and its causes is limited, and studies examining correctional populations focus on individuals in prisons. The current study extends this work by considering individuals incarcerated in jails. Using jail data from the National Inmate Survey, 2011–2012, we examine factors associated with reporting sexual victimization. We find that most incidents of sexual victimization in jails are not formally reported. Our findings suggest that primary determinates of reporting in-jail sexual assault include incident and jail environment characteristics. Implications for policy that improves reporting and prevents in-jail sexual assault are discussed.